N-terminal pro-B-type Natriuretic peptide levels and left atrial appendage thrombosis in patients with persistent atrial fibrillation - Chien Do Van; Huyen Trang Dang; Son Pham Nguyen; Minh Quang Luu (Revista Cubana de Medicina Militar)
Introduction: In hospitalized patients, atrial fibrillation is the most common arrhythmia, and leading cause of cardio-embolic stroke. Objective: To evaluate the association between N-terminal b-type natriuretic peptide pro (NT-proBNP) and left atrial appendage thrombus in persistent atrial fibrillation patients. Methods: A cross-sectional study, enrolled 139 patients with persistent non-valvular atrial fibrillation. Transthoracic and trans-esophageal echocardiographs were performed in all patients. Results: Mean age was 70.5 ± 10.6 years, 80.6% male. In patients with LAAT, NT-proBNP was positively correlated with left ventricular end diastolic diameter (LVEDD) (r=0.345), left ventricular end-systolic diameter (LVEDS) (r= 0.449), E/e' (r=0.445), and left atrial spontaneous echo contrast (LA SEC) (r=0.478), and negatively correlated with left ventricular ejection fraction (LVEF) (r=-0.473), left atrial strain (r= -0.301), strain rate (r= -0.283), and e'(r= -0.458). In patients without LAAT, NT-proBNP was positively correlated with LVEDD (r= 0.333), LVESD (r= 0.358), E (r= 0.318), E/e' (r= 0.411), left atrial volume index (LAVI) (r= 0.421), and negatively correlated with LVEF (r= -0.307). Plasma NT-proBNP (> 1279 pg/mL) could be used to predict LAAT (AUC= 0.639; Se= 67.7%, Sp= 60.2%). In patients with ejection fraction > 50%, the cutoff value of NT-proBNP to predict LAAT was 1325 pg/mL (AUC= 0.572; Se= 57.9%, Sp= 78.3%). Multiple logistic regression analysis showed that prior stroke, E/e' index, and NT-proBNP correlated with LAAT (r= 0.887; p< 0.001; r= -0.092, p= 0.035 and 0.022; p= 0.004, respectively). Conclusion: Plasma NT-proBNP levels and E/e' index are associated with LAAT in patients with persistent atrial fibrillation.